2022
DOI: 10.1039/d2an00775d
|View full text |Cite
|
Sign up to set email alerts
|

Infrared micro-spectroscopy coupled with multivariate and machine learning techniques for cancer classification in tissue: a comparison of classification method, performance, and pre-processing technique

Abstract: The visual detection, classification, and differentiation of cancers within tissues of clinical patients is an extremely difficult and time-consuming process with severe diagnosis implications. To this end, many computational approaches...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Statistical analysis utilised the pingouin package (v. 0.5.2) [ 47 ]. All classification algorithms utilised the F 1 score as the metric of performance [ 48 ]. The following sections detail each of the methodologies which were employed.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis utilised the pingouin package (v. 0.5.2) [ 47 ]. All classification algorithms utilised the F 1 score as the metric of performance [ 48 ]. The following sections detail each of the methodologies which were employed.…”
Section: Methodsmentioning
confidence: 99%
“…Of alternative technologies considered, Fourier‐transform infrared (FTIR) microspectroscopy has been recently utilised in a range of biomedical settings 11–13 . This technology allows for imaging of sample specimens at thousands of infrared (IR) wavelengths simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Although IR spectra are difficult to interpret by direct inspection, significant progress has been made by the application of machine learning techniques. [1][2][3][4][5][6] Both FTIR and Raman spectroscopy have been used to study oral squamous cell carcinoma (OSCC) (see Byrne et al 7 for a review). In particular, Fukuyama et al 8 reported that the FTIR spectra of normal tissue have stronger contributions from keratin and collagen than abnormal tissue.…”
Section: Introductionmentioning
confidence: 99%